Anatomical Core Material of the Superior Extremity Musculosceletal System for Medical Student Learning - Siti Munawaroh; Cholisa Fidduha; Nanang Wiyono; Yunia Hastami (Ahmad Dahlan Medical Journal, 2021)
Background: Anatomy education is the essential basic science as a physician to run the clinical practice. The global development leads to the transformation of the medical curriculum which then results in the reduced time allotment for anatomic learning. In musculoskeletal system, superior extremity is one of the sections having the wide range of material coverage which cannot be learned in a short length of time. As a result, the students find it difficult to learn the material. A large number of anatomic material in superior extremity musculoskeletal system which need to be learnt in a limited time underlies the researcher to conduct this research.Methods: This research employed qualitative study using two-round Delphi method. The research subjects were 20 general physicians in Indonesia selected by purposive sampling. The initial questionnaire was arranged by the researcher based on 3 anatomic textbooks, 1 research on core anatomic material, 1 research on the anatomic component of clinical orthopedic, the substance recapitulation of national anatomy curriculum, and nomina anatomica. In the first Delphi round, the panel was asked to select the component which is important to be learned based on the clinical cases as well as to add whether the component has not been written yet by the researcher. In the second Delphi round, the panel ranked from 1-4. The consensus determined by the researcher is 35%.Results: In the first Delphi round, there is no topic added yet 53 components are removed. Thus, a number of component in the first round was decreased from 510 to 457 components. The second Delphi round obtains 26 core anatomic material out of 457 topics.Conclusion: General physician consensus is 26 from the core material out of the entire anatomic material in the superior extremity musculoskeletal system. There are also clinical reasons or correlation from the material of superior extremity muscukoskeletal system which are considered important by the panels. The results obtained from the panels who come from various regions to represent the general physician in Indonesia. Keywords: anatomy; core material; Delphi method; general physician consensus; musculoskeletal system,